PENGARUH PEMINJAMAN REKAM MEDIS RAWAT JALAN TERHADAP MUTU INSTALASI REKAM MEDIS DI UPT RSUD LEMBANG - Meira Hidayati; Wiwit Rahmatika (INFOKES (Informasi Kesehatan), 2019)
This study aims to determine the influence of borrowing outpatient medical record files to quality of medical record installation at UPT RSUD Lembang The method used is a quantitative research method with a descriptive approach. Data collection techniques used are the method of observation, questionnaires and are equipped with a literature review. The sampling technique uses saturated sampling technique with a sample of 11 Medical Record Officers. The results of the calculations performed using a questionnaire with a simple linear test model, the number of samples N = 11 and significance α = 5% obtained tcount = 7.384 and t table = 1.833 the results is t count> t table then H0 is rejected and H1 is accepted, that means borrowing medical records influential outpatient on the quality of medical record installations at the UPT RSUD Lembang. The effect is 86% and 14% is influenced by other variables or errors (e). From the research conducted, problems found include: (1) The absence of outguide instructions when borrowing outpatient medical records at the medical record storage rack, (2) There is no handover at the time of return of medical record, (3) There are still delays in returning medical records and (4) There are still medical records that have not been stored in the medical record storage rack. Based on research conducted, researchers provide advice to the hospital as follows: (1) The existence of the SOP socialization Sso that medical record return in a timely manner, (2) Efforts to arrange a good medical record storage system, accelerate the service so that it does not cause patients to wait a long time (3) Imposing strict sanctions against officers so there is no misunderstanding of the existence of borrowed medical records, (4) The hospital shall use an outguide so that the medical record is clear of its existence